In vitro effects of environmental isolates of Acanthamoeba T4 and T5 over human erythrocytes and platelets - Alvarado Ocampo, Johan (2020)
Free-living amoebae of the genus Acanthamoeba have been associated with keratitis and encephalitis. Some factors related to their pathogenic potential have been described, including the release of hydrolytic enzymes, and the adhesion and phagocytosis processes. However, other factors such as their effect over the hemodynamics and microcirculation elements have not been fully investigated. This work determines the in vitro activity of potentially pathogenic environmental isolates of Acanthamoeba genotype T4 and T5 over erythrocytes and platelets. The hemolytic activity (dependent and independent of contact), as well as the production of ADP of ten environmental isolates of Acanthamoeba obtained from dental units, combined emergency showers, dust, and hospital water, were measured. Tests were carried out over erythrocytes in suspension and blood agar plates, incubated at 4 °C, room temperature and 37 °C. Erythrophagocytosis and platelet aggregation assays were also performed. Live trophozoites of all of the isolates tested showed a hemolytic activity that was temperature dependent. Over erythrocytes in suspension, variable hemolysis percentages were obtained: a maximum of 41% and a minimum of 15%. Regarding hemolysis over agar plates, two patterns of hemolysis were observed: double and simple halos. Conditioned medium and crude extracts of trophozoites did not show hemolytic activity. Erythrophagocytosis by Acanthamoeba was also observed; however, no production of ADP was determined by the employed methodology.